Historiografi Tafsir Era Klasik: Dinamika Penafsiran Al-Qur`An Dari Masa Nabi Hingga Tâbi’în - Hilmy Pratomo (Fakultas Syari'ah dan Hukum (FSH) UNSIQ, 2020)
The interpretation of the Koran is an effort without ever reaching the point of stopping, In every time and place, it always present interpreters with different styles, methodologies and different characteristics. Husein al-Dzahabi mapping the tafsir for three phase, phase Muhammad and his friends (sahabat), tabi’in (friends of sahabat). This paper deal with history tafsir from Muhammad phase to the codification phase. The main problem will be studied in this paper is trying to analyze development interpretation Koran to view the flow of interpretation in terms of methodological aspects and approach interpreting the Koran.